Schule der Gefühle: Zur emotionalen Erfahrung von Minderwertigkeit in neoliberalen Zeiten - Wellgraf, Stefan (transcript, 2018)
People suffering from marginalization only rarely experience it abstractly in relation to structures of social inequality but instead experience it rather emotionally: School children attending "Hauptschule", the lowest level of secondary education in Germany, are angry at their teachers and bored with school; they are embarrassed about their grades and afraid of not finding a job later in life. Stefan Wellgraf`s multi-layered ethnography of a school in Berlin-Neukölln focuses on the pupils` emotional experiences and suggests that emotions be read in a political manner.